Pengaruh Persepsi Harga, Service Excellence, dan Inovasi Layanan terhadap Kepuasan Penumpang Bus Super Executive Primajasa Perusahaan Otobus (PO) Tasikmalaya - Salsa Salsa; Agung Pramudya (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
This study aims to analyze the influence of price perception, service excellence, and service innovation on passenger satisfaction of Bus Super executive Primajasa PO Tasikmalaya. The research was motivated by a ticket sales decline phenomenon and pre-survey findings indicating that passenger satisfaction still needs improvement. This study employed a quantitative approach with Bus Super executive Primajasa passengers as the research subjects, and data collection techniques using questionnaires and documentation. Data analysis was conducted descriptively and verificatively using multiple regression analysis. The results showed that all variables were in the feasible category, with price perception (0.7558), service excellence (0.7812), service innovation (0.7536), and passenger satisfaction (0.7856). Partially, price perception (t count = 5.565; sig. 0.000), service excellence (t count = 6.352; sig. 0.000), and service innovation (t count = 5.356; sig. 0.000) have a significant effect on passenger satisfaction. Simultaneously, these three variables also have a significant effect (F count = 49.045; sig. 0.000) with a contribution of (R² = 0.615). This study concludes that improving price perception, service excellence, and service innovation together can encourage passenger satisfaction, so the company needs to maintain and improve these three aspects in order to maintain customer loyalty amidst competition in intercity transportation services.